Association of the Interleukin-10-592C/A Polymorphism and Cervical Cancer Risk: A Meta-Analysis. (12th July 2022) - Diakite, Brehima; Kassogue, Yaya; Maiga, Mamoudou; Dolo, Guimogo; Kassogue, Oumar; Musa, Jonah; Morhason-Bello, Imran; Traore, Ban; Traore, Cheick Bougadari; Kamate, Bakarou; Coulibaly, Aissata; Bah, Sekou; et al.
Abstract : A literature review showed some discrepancies regarding the association of -592C/A with the risk of cervical cancer. To allow more precise analysis of the data by increasing the number of cases studied and more acceptable generalization by considering results from different sources, the present meta-analysis was performed on available published studies that explored the relationship between SNP -592C/A of the IL-10 gene and the risk of cervical cancer. Eleven available studies, including 4187 cases and 3311 controls, were included in this study investigating the relationship between the -592C/A polymorphism of IL-10 and cervical cancer risk. Fixed-effects or random-effects models were performed with pooled odds ratios (ORs). Heterogeneity and bias tests were performed by the inconsistency test and funnel plot, respectively. The overall analysis showed an increased susceptibility to cervical cancer with the -592C/A polymorphism of the IL-10 gene for the recessive model (OR = 1.30, 95% CI = 1.14–1.49), dominant model (OR = 1.36, 95% CI = 1.09–1.70), and additive model (OR = 1.25, 95% CI = 1.09–1.44). Regarding ethnicity, a significant association of the -592C/A polymorphism of the IL-10 gene was linked to an elevated risk of cervical cancer for all genetic models (recessive, dominant, and additive) in the Asian populations and for the recessive and additive models in Caucasians with P < 0.05 . The -592C/A polymorphism of the IL-10 gene may be considered a risk factor for cervical cancer.